The social Function of mental health, alcoholand other drugs services: the contributions of aplied psychoanalysis (Research, Society and Development, 2022)
This article reports the result of the research that asked about the possible contribution of psychoanalysis applied to social function of Mental Health, Alcohol and Other Drugs Services in Belo Horizonte/Minas Gerais, according to what is recommended in public health policies. It presents as a general objective, investigate the work done by professionals guided by psychoanalysis, in Northwestern Children's Mental Health Reference Center and Rua Noroeste Office. The work was developed through qualitative research, that way of working that does not interfere with the psychoanalytic orientation present at the base of the investigation, the information was obtained through semi-structured interviews, which favor free association.  Three higher-level professionals from each Service were interviewed. Freudian and Lacanian psychoanalysis were the guidelines for data analysis. Concluded that applied psychoanalysis contributes to the social function of the researched Services, through clinical treatment, promoting social inclusion, intersectoral actions and strengthening family and community ties. And that, although psychoanalysis is the target of criticism about its efficiency in treatments within institutions she lives on through other speeches.